Editorial: Storage of Information on Neuronal DNA; a Novel Logical Notion - Haque, Anwar Ul (International Journal of Pathology, 2020)
Man (Both man and woman) is the crown of God’s creature. He has been given man the ability to acquire, retain and reproduce immense knowledge as has been well described in the final ever fresh and ever preserved divine book Quran.1 This capability was demonstrated in front of the angels and then angels were ordered to prostrate in front of Adam. All angels did but the Satan who was although not an angel but used to spend time among them refused to do so. He was arrogant and asked permission from the God to allow him to make man go astray. The permission was granted as the God had given enough intellect and wisdom to man to stay away from being slave of the Satan.1 Where that information of all things was stored in Adam’s brain, is still a big question. An although we do have all that information, but we can’t reproduce that, and we have to re-search that knowledge.